POLEMIK PENGAKUAN TANAH ULAYAT DALAM HUKUM NASIONAL MASYARAKAT ADAT DI PAPUA - Alfi Mufida; Arista Nureka Ramadhina; Dhea Fitria Puspitaningrum; Fatimah Siti Umairoh (Pojok Publisher, 2025)
This study examines the challenges and implications of national legal recognition of customary land rights Indigenous Territorial Rights for indigenous communities in Papua, Indonesia. The research employs a descriptive qualitative methodology, focusing on legal and social analyses to evaluate how national recognition impacts the rights of these communities. The findings reveal that despite constitutional acknowledgment, the enforcement of Indigenous Territorial Rights often faces significant obstacles, particularly in resource-rich regions like Papua. Conflicts arise due to ambiguous regulations and competing national interests that prioritize economic development over indigenous rights. The government plays a critical role in recognizing and protecting Indigenous Territorial Rights through various laws, such as the Special Autonomy Law No. 21/2001 for Papua. However, its actual implementation frequently fails to meet local expectations, leading to social and legal disputes. Furthermore, indigenous groups actively pursue recognition of their territorial rights through collective action and legal advocacy, reflecting their resilience in preserving ancestral heritage. Ultimately, while a legal framework exists, there remains an urgent need for fair and effective enforcement of Indigenous Territorial Rights to ensure the socioeconomic well-being of Papua’s native populatio.